Objectives Of Educational Sponsorship as a Marketing Communication Tool and Its Application at the Sate Oil Company of Azerbaijan Republic/ SOCAR - Abutalibov, Rasim; Guliyev, Seymur (Видавництво Львівської політехніки, 2013)
The aim of this article is to provide a better understanding of educational sponsorship and its application as a marketing communication tool in SOCAR. So as to reach the aim, research question focuses on the objective of educational sponsorship. Author used a qualitative research with a case study. The interviews and documentations were used as primary and secondary data. The common outcome of the study is that several objectives of educational sponsorship are generally used. The most frequently used objectives of educational sponsorship are corporate related objectives, such as corporate image, increasing community involvement, employee relations and public perceptions.
Keywords: Sponsorship; corporate image; marketing objective; educational objectives; marketing communications; media; community involvement